Development theories and development experience: Half a century journey - Vladimir Popov (Transformation, Integration and Globalization Economic Research (TIGER), 2011)
This paper examines the impact that development theories have had on development policies, and the inverse impact of actual successes and failures in the global South on development thinking. It is argued that development thinking is at the cross-roads. Development theories in postwar period went through a full circle - from Big Push and ISI to neo-liberal Washington consensus to the understanding that neither the former, nor the later really works in engineering successful catch-up development. Meanwhile, economic miracles were manufactured in East Asia without much reliance on development thinking and theoretical background - just by experimentation of the strong hand politicians.
Keywords: 330